Effectiveness of different bathing methods on physiological indexes and behavioral status of preterm infants: a systematic review and meta-analysis - Xing Sun; Jiayi Xu; Ruhua Zhou; Beibei Liu; Zejuan Gu (BMC, 2023)
Abstract Background Bath is an external stimulus for preterm infants. Currently, three methods are used for preterm infants to bath. It is important to choose the best way for them. The objective of this meta-analysis is to evaluate the effectiveness of different bath methods on physiological indexes and behavioral status of preterm infants. Methods This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses [PRISMA] guidelines and was registered in PROSPERO(CRD42022377657). PubMed, Embase, Cochrane Library, Web of Science, CINAHL, Sino Med, China National Knowledge Internet (CNKI) and Wan-Fang database were systematically searched for randomized controlled trials on the effects of different bath methods for preterm infants. The retrieval time was from the establishment of the database to February 2023. According to the inclusion and exclusion criteria, the literature was screened, quality evaluated and the data was extracted. Reman Version 5.4 was used for meta-analysis and Stata 16.0 software for publication bias Egger's test. Results A total of 11 RCTs with 828 preterm infants were included. The results of meta-analysis showed that the body temperature and oxygen saturation of preterm infants in the sponge bath group were lower than those in conventional tub bath group (SMD = -0.34; 95%CI -0.56 to -0.12; I2 = 0; p < 0.01), (MD = -0.39; 95%CI -0.76 to -0.02; I2 = 39%; p = 0.04), while the heart rates were higher than those in conventional tub bath group(MD = 5.90; 95%CI 0.44 to 11.35; I2 = 61%; p = 0.03). Preterm infant's body temperature and blood oxygen saturation of in swaddle bath group were higher than those in conventional tub bath group (MD = 0.18; 95%CI 0.05 to 0.30; I2 = 88%; p < 0.01), (MD = 1.11; 95%CI 0.07 to 2.16; I2 = 86%; p = 0.04), respiratory rates were more stable compared with infants in conventional tub bath group (MD = -2.73; 95%CI -3.43 to -2.03; I2 = 0; p < 0.01). The crying duration, stress and pain scores of preterm infants in swaddle bath group were lower than those in conventional tub bath group (SMD = -1.64; 95CI -2.47 to -0.82; I2 = 91%; p < 0.01), (SMD = -2.34; 95%CI -2.78 to -1.91; I2 = 0; p < 0.01), (SMD = -1.01; 95%CI -1.40 to -0.62; I2 = 49%; p < 0.01). Egger's test showed no publication bias in body temperature, respiratory rate, oxygen saturation, and crying duration. Conclusions Swaddle bath is the best bathing method than conventional tub bath and sponge bath in maintaining the stability of preterm infant's body temperature, blood oxygen saturation and respiratory rate. In addition, swaddle bath also plays a role in reducing cry duration, stress scores, and pain levels of preterm infant compared with conventional tub bath and sponge bath. However, due to the important heterogeneity in some outcomes, future studies with larger sample size and more appropriately design are needed to conduct before recommendation. Trial registration Prospero CRD42022377657